2018
DOI: 10.1093/pubmed/fdy174
|View full text |Cite
|
Sign up to set email alerts
|

Health and mass unemployment events—developing a framework for preparedness and response

Abstract: BackgroundMass unemployment events are not uncommon yet the impact on health is not well recognised. There is a need for a preparedness and response framework, as exists for other events that threaten population health.MethodsFramework informed by a narrative review of the impact of mass unemployment on health (studies published in English from 1990 to 2016), and qualitative data from 23 semi-structured interviews with individuals connected to historical national and international events, addressing gaps in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…20,21 The quality of the local labour market can also affect the wider community through reduced spending power and decline in community participation. 5,22 Considering the wider-reaching social and wellbeing implications of precarious employment, it has been suggested that precarious employment is now an emerging social determinant of health. 6 It is relatively unknown whether the association(s) between precarious employment and poor health is the same across groups at risk of precarious employment, that is, is the health impact of precarious employment worse for some than others.…”
Section: Review Papermentioning
confidence: 99%
“…20,21 The quality of the local labour market can also affect the wider community through reduced spending power and decline in community participation. 5,22 Considering the wider-reaching social and wellbeing implications of precarious employment, it has been suggested that precarious employment is now an emerging social determinant of health. 6 It is relatively unknown whether the association(s) between precarious employment and poor health is the same across groups at risk of precarious employment, that is, is the health impact of precarious employment worse for some than others.…”
Section: Review Papermentioning
confidence: 99%
“…Global estimates suggest that up to 25 million jobs could be lost as a result of the COVID-19 pandemic. 3 Typically, mass unemployment events disproportionately impact the younger and older age groups, [4][5][6] and those with lower skills or underlying health conditions are at more risk of exiting the labour market in the longer term. Compared with other Western countries, the USA and the UK have experienced more severe immediate labour market impacts.…”
Section: Introductionmentioning
confidence: 99%
“…14 Identifying the groups most vulnerable to changes in employment during the COVID-19 pandemic is important to better develop and target the health, re-employment and social support needed to prevent a longer term detrimental impact on societal health. 4 Emerging UK research has raised concerns about the disproportionate impact on specific demographic groups, 10 11 15 while also commenting on regional disparities, 15 suggesting a need for different approaches in the postpandemic recovery. We investigated the impact of COVID-19 on employment in the initial phases of the pandemic as well as observed differences by underlying health and household financial security in Wales.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the scatter plot shows that the differentiation was serious, which was mainly related to the individual's physical quality, personal will and survival belief [61].…”
Section: On Mortality-to-incidence Ratiomentioning
confidence: 99%